CT SCAN UROGRAPHY EXAMINATION PROCEDURE WITH CLINICAL HYDRONEPHROSIS IN THE RADIOLOGY INSTALLATION OF AWAL BROS PANAM HOSPITAL - Irvandy Febrian; Neng Asih (Medical Imaging and Radiation Protection Research Journal, 2024)
Background: Hydronephrosis is a condition characterized by dilation of the pelvis and renal calyces due to impaired or obstructed urine flow. CT urography can provide more comprehensive anatomical information about the urinary tract and help evaluate the cause and degree of dilation of the pelvicalyceal system. In clinical practice, the examination procedure may be adjusted, including the use of oral hydration without the administration of diuretics. This study aimed to determine the CT urography examination procedure in patients with clinical hydronephrosis at the Radiology Department of Awal Bros Panam Hospital. Methods: The study used a descriptive qualitative method with a case study approach. Data were collected through direct observation, interviews, and documentation of the CT urography examination procedure. The study subjects consisted of two radiographers and one radiologist. Data were analyzed descriptively using triangulation techniques. Results: The examination was performed without the administration of diuretics. Patients were advised to increase their fluid intake and to refrain from urinating until the bladder was full. The examination was performed in the supine position, using the head-first method, using a helical abdominal protocol with a scanning range from the xiphoid process to the symphysis pubis. Images were reconstructed in axial, sagittal, and coronal planes. The use of oral hydration and urinary retention can help improve visualization of the urinary tract and provide adequate diagnostic information. Conclusion: CT scan urography procedures for hydronephrosis cases at Awal Bros Panam Hospital can be performed without diuretics by utilizing oral hydration and bladder filling through urinary retention.